MAPPING THE INTERDISCIPLINARY LANDSCAPE OF DIGITAL ROMANTIC FRAUDS USING VOS VIEWER - Ronal Kamim; Arum Karisma Nadya Lakshita; Dwi Permana Putra; Hendro Margono (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2025)
Romance fraud is a crime committed through emotional manipulation via digital platforms, causing significant financial and psychological harm to victims. Despite growing prevalence, the phenomenon lacks unified terminology, with terms such as